Integrating augmented reality with the e-IM3 structured thinking model to enhance problem-solving skills and learning interest in elementary spatial geometry - Maulana, Abas; Murtafiah, Wasilatul; Handhika, Jeffry; Alvares, Joel I. (Universitas Hamzanwadi, 2025)
This study addresses the need to improve fifth-grade students’ problem-solving skills and learning interest in spatial geometry—a topic often perceived as abstract and challenging—by developing an Augmented Reality (AR)-based instructional medium integrated with the e-IM3 (intelligent, meaningful, mindful, joyful) model. Grounded in the ADDIE framework, the research encompassed the analysis, design, development, implementation, and evaluation phases at SDN Kwadungan Lor, Ngawi, East Java. Initial analysis via diagnostic tests and teacher interviews confirmed low baseline performance and motivation levels. The resulting AR-e-IM3 media underwent expert validation and readability testing, achieving high validity scores (media: 3.79; problem-solving instrument: 3.42; and interest instrument: 3.98). A limited trial (n = 10) and a large-scale trial (n = 32) demonstrated strong practicality (88% and 84.5%, respectively). Effectiveness was evidenced by moderate N-Gain improvements in problem-solving skills (0.58 and 0.51) and learning interest (0.63 and 0.51). These findings indicate that the AR-e-IM3 integration successfully fosters engagement and meaningful learning, aligning with Generation Alpha’s digital learning preferences. This study underscores the potential of technology-enhanced affective–cognitive models in elementary mathematics education. The implications include the scalable adoption of such media to strengthen 21st-century competencies—particularly critical thinking, spatial reasoning, and intrinsic motivation—while supporting curriculum innovation in resource-constrained settings.